Woman's role in economic development : with a new introduction by Nazneen Kanji, Su Fei Tan and Camilla Toulmin. - Boserup, Ester [et.al.] (Earthscan, 2007)
A documented investigation into what happens to women in the process of economic and social growth throughout the Third World. Covering Africa, Latin America and Asia, it studies the role of women in the development and modernization of poor countries.